Interaksionisme Simbolik dan Fenomena Bystander Masyarakat dalam Kelola Sampah - Dwiki Faiz Sarvianto (Jurnal Neo Societal, 2025)
Individual behavior in waste management is very important to overcome waste generation. Several studies related to waste management behavior state that individual knowledge and attitudes are related. However, both are not always positively related. The purpose of this study is to analyze the factors causing the disconnection between knowledge and attitudes as the focus of attention so that changes in community behavior that lead to environmentally friendly behavior can be formed. This study was written with a qualitative approach through a descriptive analysis method with literature study techniques. The result, between knowledge and attitude, there is a decision to take waste management actions from individuals based on the results of the meaning (perception) due to symbolic interactionism and individual interests. Not only that, bystander effect symptoms have the potential to be found because the attitude of individuals will be influenced by the social environment/surrounding support. In conclusion, in the context of waste management, if you want to change the behavior of an environmentally friendly community, then in addition to physical support/facilities, perception, interest, and social support are important things to consider.